Mental health interventions: an integrated system based on generative artificial intelligence and virtual reality - Attilio Della Greca; Ilaria Amaro; Paola Barra; Enrico Madonna; Paloma Díaz; Ignacio Aedo; Genoveffa Tortora (Virtual Reality, 2026)
Abstract Mental health interventions use therapeutic techniques to support emotional well-being, often leveraging emerging technologies to improve accessibility and effectiveness. In recent years, tools such as VR and AI have been increasingly used to create immersive and adaptive therapeutic experiences. This paper presents a framework that integrates generative artificial intelligence (GenAI) and virtual reality (VR) to enhance mental health interventions. The system allows for near real-time co-creation of three-dimensional objects during therapy sessions and provides a customizable “safe space”for emotional regulation. In a user study (n = 30), participants completed anxiety (GAD-7) and depression (PHQ-9) assessments, generated virtual objects linked to specific emotions, and rated the system’s usability (SUS) and recommendability (NPS). The framework achieved a high SUS score of 79 and an NPS of 40, indicating robust usability and willingness to recommend. Notably, neither anxiety nor depression levels, nor prior experience with VR or GenAI, significantly affected these measures. These findings highlight the feasibility and acceptability of combining GenAI and VR to offer immersive, personalized, and user-friendly therapeutic environments, representing a promising direction for future clinical validation in people-centered healthcare programs.